2005
DOI: 10.1197/j.aem.2005.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Emergency Contraception in Massachusetts Emergency Departments

Abstract: There was significant variability in access to EC in Massachusetts EDs and in services for sexual assault survivors. Hospital type and provider preference affected availability. This study suggests that access to EC is limited, and that there are not consistent services for women seeking EC, including for victims of sexual assault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Many Catholic institutions limit reproductive healthcare options based on religious doctrines and these limitations have health repercussions [1][2][3][4][5][6][7][8]. At one Jesuit hospital, limitations on immediate postpartum contraception in the form of depot medroxyprogesterone acetate resulted in higher repeat pregnancy rates for adolescents and young adult women [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Catholic institutions limit reproductive healthcare options based on religious doctrines and these limitations have health repercussions [1][2][3][4][5][6][7][8]. At one Jesuit hospital, limitations on immediate postpartum contraception in the form of depot medroxyprogesterone acetate resulted in higher repeat pregnancy rates for adolescents and young adult women [2].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients cared for at Catholic hospitals has also increased over the past two decades as the number of mergers increased; in 2011, 10 of the top 25 health systems in the United States were Catholic [1]. When women are cared for at Catholic owned hospitals they face several restrictions to reproductive health care including access to birth control methods, emergency contraception, and miscarriage management [1][2][3][4][5][6]. Many obstetrician-gynecologists (OB/ GYNs) who practice at religiously affiliated institutions have reported conflicts with religious policies for patient care, deemed some of these restrictions to be unacceptable when caring for women, and/or reported that such restrictions have interfered with clinical management [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with four prior studies that explored EC provision by ED physicians in adult ED settings. 12,13,15,16 Specifically, contrary to Society of Adolescent Medicine, 29 American Academy of Pediatrics, 30 and American College of Obstetricians and Gynecologists 31 recommendations, 20% of directors do not always offer EC as part of sexual assault care. This failure to offer EC, both in cases of sexual assault and consensual unprotected sex within the 120 hours following intercourse, may result in negative outcomes such as unwanted pregnancy and associated hardships.…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have documented the differences between EC services in Catholic versus non-Catholic EDs in terms of offering EC onsite, 11,12,13,15 prescribing EC to non-rape patients, 15 and EC counseling practices. 36 Fewer directors who worked in Catholic-affiliated hospitals in our study reported discussing EC in the past year than did directors who worked in non-Catholic hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation